Particle Size and Humidity Effects on Nanocellulose Adhesion to Glass: Implications for Mitigating Particulate Contamination in Industrial Processes - Lin, Yen-Ting; Walczak, Wanda; Banerjee, Joy; Smith, Nicholas J.; Agnello, Gabriel; Zoba, Ava N.; Manley, Robert; Kim, Seong H. (ACS applied nano materials, 2022)
Particulates adhered to glass surfaces can result in manufacturing defects during display module fabrication. The adhesion force is highly sensitive to the water meniscus formed in humid environments and can be examined experimentally as a function of relative humidity using atomic force microscopy by measuring the pull-off force between a flat glass surface and either a spherical or a cone-shaped probe tip. In this work, the effective thickness and hydrogen bonding interaction of adsorbed water were probed using transmission FTIR at Brewster’s angle with p-polarized light, investigating two different multicomponent glass surfaces subject to different aqueous treatments. The effective thickness of water layers so measured was used to estimate the curvature of the water meniscus at the particulate–glass interface, thereby enabling the prediction of the adhesion forces exerted on the nanoparticles and microspheres in pull-off measurements. Correlations between the adsorbed water layer, the electrostatic charging, and the adhesion force of cellulosic materials to glass from the nanoscale to the microscale are discussed in this work, which provide insights into mitigating particulate contamination in industrial processes.